In vitro modulation of multidrug resistance by pregnane steroids and in vivo inhibition of tumour development by 7α-OBz-11α(R)-OTHP-5β-pregnanedione in K562/R7 and H295R cell xenografts. (1st January 2019) - Alameh, Ghina; Emptoz-Bonneton, Agnès; Rolland de Ravel, Marc; Matera, Eva L.; Mappus, Elisabeth; Balaguer, Patrick; Rocheblave, Luc; Lomberget, Thierry; Dumontet, Charles; Le Borgne, Marc; Pugeat, Michel; Grenot, Catherine; et al.
Abstract: Synthetic progesterone and 5α/β-pregnane-3, 20-dione derivatives were evaluated as in vitro and in vivo modulators of multidrug-resistance (MDR) using two P-gp-expressing human cell lines, the non-steroidogenic K562/R7 erythroleukaemia cells and the steroidogenic NCI-H295R adrenocortical carcinoma cells, both resistant to doxorubicin. The maximal effect in both cell lines was observed for 7α- O -benzoyloxy, 11α(R)- O -tetrahydropyranyloxy-5β-pregnane-3, 20-dione 4 . This modulator co-injected with doxorubicin significantly decreased the tumour size and increased the survival time of immunodeficient mice xenografted with NCI-H295R or K562/R7 cells.